Pharmacogenetics of selective serotonin reuptake inhibitors in pediatric depression and anxiety. (November 2008) - Kronenberg, Sefi; Frisch, Amos; Rotberg, Beni; Carmel, Miri; Apter, Alan; Weizman, Abraham
Selective serotonin reuptake inhibitors (SSRIs) are now an accepted and widely used first-line treatment for pediatric depression and anxiety. However, the data indicate that SSRI treatment achieves a clinical response in only 55––60% of children, and some may develop drug-induced suicidal behavior. Clinicians have no reliable tools to help them identify in advance those youths who are not likely to respond to an SSRI, or who are likely to develop SSRI-induced suicidality. Pharmacogenetic research attempts to identify genetic markers that are associated with response and side-effect profile. This review covers all the pharmacogenetic studies conducted as yet on pediatric samples and compares them with available data on adult samples. An emphasis is put on serotonergic genes such as the serotonin transporter ( 5-HTT ) and additional genes known to be active in the CNS.